Cross-sectional study of population-specific streptococcal antibody titres in Uganda. Issue 9 (29th June 2020) - Okello, Emmy; Murali, Meghna; Rwebembera, Joselyn; Atala, Jenifer; Bowen, Asha C; Harik, Nada; Kaudha, Gloria; Kitooleko, Samalie; Longenecker, Chris; Ndagire, Emma; Omara, Isaac Otim; Oyella, Linda Mary; et al.
Abstract : Objective: Despite substantial variation of streptococcal antibody titres among global populations, there is no data on normal values in sub-Saharan Africa. The objective of this study was to establish normal values for antistreptolysin O (ASO) and antideoxyribonuclease B (ADB) antibodies in Uganda. Design: This was an observational cross-sectional study. Setting: This study was conducted at Mulago National Referral Hospital, which is located in the capital city, Kampala, and includes the Uganda Heart Institute. Patients: Participants (aged 0–50 years) were recruited. Of 428 participants, 22 were excluded from analysis, and 183 (44.4%) of the remaining were children aged 5–15 years. Main outcome measures: ASO was measured in-country by nephelometric technique. ADB samples were sent to Australia (PathWest) for analysis by enzyme inhibition assay: 80% upper limit values were established. Results: The median ASO titre in this age group was 220 IU/mL, with the 80th percentile value of 389 IU/mL. The median ADB titre in this age group was 375 IU/mL, with the 80th percentile value of 568 IU/mL. Conclusions: The estimated Ugandan paediatric population standardised 80% upper-limit-of-normal ASO and ADB titres is higher than many global populations. Appropriateness of using population-specific antibody cutoffs is yet to be determined and has important implications for the sensitivity and specificity of rheumatic fever diagnosis.